STUDY REGARDING THE DETERMINATION OF THE LEVEL OF SOMATIC INDICES AND THE MOTOR POTENTIAL OF THE SECONDARY SCHOOL STUDENTS AT "AURELIAN STANCIU" SCHOOL IN SALCEA, SUCEAVA COUNTY - Ionel Bădeliță; Florin Leuciuc (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
The paper deals with a constantly updated topic, namely the ability of physical and motor development of young people, especially the one regarding the potential of the school population in pre-university education. The aim of this study was to make a somatic and motor model of the secondary school student at ,,Aurelian Stanciu" Secondary School in Salcea, that can be used to form representative school teams in different sports, and to support teachers in sports clubs and high schools for a possible selection campaign for performance sports. The duty of the Physical Education teacher is to make students aware of the beneficial effect of the physical exercise in relation to the state of health, growth, development and evolution in the natural parameters of the body related to age and sex, being important as well the way he explains and makes himself clear in the group of students he works with.